+0  
 
0
63
2
avatar

Simplify :

sin(3t+π)+2cos(3t)

 
Guest Aug 11, 2017
social bar

Best Answer 

 #2
avatar+6765 
+2

\(\sin(3t+\pi)+2\cos(3t)\\ =\sin(3t)\cos(\pi)+\cos(3t)\sin(\pi)+2\cos(3t)\\ =\sin(3t)\cdot(-1)+0+2\cos(3t)\\ =2\cos(3t)-\sin(3t)\)

 
MaxWong  Aug 11, 2017
Sort: 

2+0 Answers

 #1
avatar
0

= 2cos(3t) - sin(3t)

 
Guest Aug 11, 2017
 #2
avatar+6765 
+2
Best Answer

\(\sin(3t+\pi)+2\cos(3t)\\ =\sin(3t)\cos(\pi)+\cos(3t)\sin(\pi)+2\cos(3t)\\ =\sin(3t)\cdot(-1)+0+2\cos(3t)\\ =2\cos(3t)-\sin(3t)\)

 
MaxWong  Aug 11, 2017

14 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details